Analisis Positioning Institutional dan Saluran Komunikasi dalam meningkatkan Keunggulan Basing Perguruan Tinggi Swasta di Kota Medan: Studi Analisis PTS Kota Medan di Universitas Muslim Nusantara Al-Washliyah - Hardi Mulyono; Muhammad Hilman Fikri (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the strategic mechanisms for building competitive advantage in higher education institutions through a holistic approach that includes institutional positioning, communication channels, and value perception formation at the Universitas Muslim Nusantara Al-Washliyah. Using Structural Equation Modeling (SEM) with Partial Least Square (PLS) method, the study involved 361 respondents from various stakeholder groups. The results show that institutional positioning (coefficient 0.372) and communication channels (coefficient 0.411) have a significant impact on value perception formation. These two variables directly influence the university's competitiveness, with contributions of 0.287 and 0.245, respectively. Additionally, value perception proved to play a strong mediating role with an influence coefficient of 0.386. These findings emphasize the importance of an integrated and comprehensive marketing strategy in facing the contemporary higher education competition, highlighting institutional differentiation, responsive communication, and the creation of a positive value perception. This study provides both theoretical contributions and practical implications for higher education managers to improve their competitive position in the education market.